Reliability modeling of multiple performance based on degradation values distribution. (October 2016) - Li, Haiqing; Li, Ruizhi; Li, Haowei; Yuan, Rong
In practical engineering, reliability analysis of products plays an important role in assessing the corresponding remaining life. Products often have more than one failure mechanism, which means reliability should be evaluated by two or more performance characteristics. To resolve the above problem, based on the degradation values distribution method utilization, copula functions as the link functions of their marginal distributions are introduced in this study. The performance characteristics are also considered the dependent as well as independent to make a comparison. Moreover, a framework for reliability assessment of products with the multiple performance degradation is developed. Finally, the proposed methodology and model is validated effectively by the fatigue cracks data from the literature. From the results, we can see that the proposed model is more accurate.